Predictors of independence in older people: A longitudinal, population-based study using the CARE75 + cohort - Emily Taylor; Victoria A Goodwin; Andrew Clegg; Lesley Brown; Julia Frost; Susan Ball (BMC Geriatrics)
Abstract Background The ability to predict older people’s functional independence has implications for the development and provision of services to improve individual sense of self and wellbeing. Methods Using linear regression analyses we identified predictors of independence, measured using the Nottingham Extended Activities of Daily Living (NEADL) scale, at 12 and 24-months from baseline. Data were obtained from 1277 community-dwelling people aged ≥ 75. Multivariable models included predictors that were selected through review of existing literature, perspectives of older people, and univariable analyses. Multiple imputation was used to account for missing data. Results Participants’ mean age was 84.61 years (SD 4.95) and just over half were female (n = 655, 51.29%). At baseline, participants had a mean NEADL score of 53.82 (SD 13.19). Younger age, fewer hours of informal help received, no registered visual impairment, lower frailty, living alone, higher cognitive function, greater physical function, absence of depression, and higher baseline NEADL were significant predictors of greater independence at 12-months. Younger age, higher baseline NEADL score, living alone, less frailty, higher cognitive function, alcohol consumption, greater physical function, and absence of depression predicted greater independence at 24-months. Conclusion Depression and frailty are important predictors of an older person’s independence with other variables such as activities of daily living, age, cognitive function, alcohol consumption, and living status also having an impact over a prolonged period. Refining understanding of the mechanisms within frailty and depression is likely to improve targeting of support and interventions, which will have a lasting impact on older people’s independence.